Study of Pilavai Rogam in Siddha Medicine - Sukantha, P.; Nirushini, K.; Pancharajah, S.; Thayalini, T. (University of Jaffna, 2020)
Aruvai Maruthuvam is one of the division of Siddha Medicine. It deals with Kaddee, Pun, Pavunthiram, Seelkaddee and Pilavai. Pilavai is classified under Pilavai roga nithanam, which was mentioned in the text of Pararasasekaram. The definition of pilavai is a swelling in the back side of the body which form yellow colour discharge and also affects the mamisathathu (muscle). Pilavai is mentioned in many Siddha books even though all the details such as definition, cause, types, sites, clinical features, complications are not mentioned in all literatures. Carbuncle is red swollen and painful cluster of boils that are connected to each other under the skin, which is caused by infection (Staphylococcus aureus bacteria) and occurs in hairyarea. Diabetes, kidney diseases, Liver disease are risk factors to carbuncle. Its main clinical features are multiple opening on skin, abscess formation, ruptureand oozing. The aim of the study is to review the pilavainoi from different Siddha literatures. Eight books were selected from the library of Unit of Siddha Medicine. Data were collected, tabulated and analysed. Only one literature mentioned that the infection is a cause for pilavai. Seventeen types of pilavai noi were identified from the review. Out of eight literatures, six texts (75%) mentioned about pakka pilavai. All the literature (100%) mentioned that the back of the shoulder and vertebral region are most common sites for the formation of pilavai. Only one book by Segarasasekaram mentioned about the premonitory sign that is redness and forming depression on the skin. Out of eight literatures 2 texts (25%) mentioned common symptoms of pilavai. Sixteen symptoms were identified. The swelling, pus collection, ruptured with many holes are the main clinical features of pilavainoi. Three texts (37.5%) mentioned symptoms of Petiyapilavai. Eleven symptoms were identified. Thus the definition, sites, cause, clinical features, risk factors of pilvainoi may be correlated with the carbuncle.
Keywords: Pilavainoi; Periyapilava; Pakkapilavai; Siddha literatures; Carbuncle